Determination of the isentropic turbine efficiency due to adiabatic measurements and the validation of the conditions via a new criterion. (December 2018) - Zimmermann, R; Baar, R; Biet, C
The determination of the isentropic turbine efficiency under adiabatic and SAE boundary conditions is studied in this paper. The study is structured into two parts. The first part describes the possibility of measuring the isentropic turbine efficiency directly. Normally this is not possible in measurements conducted following the SAE J922 guidelines. Therefore, the experiments have been carried out under adiabatic conditions, and combined with improved measuring equipment. The results were compared with adiabatic computational fluid dynamics simulations of this turbocharger. In the second part, a new criterion is defined in order to evaluate the quality of the adiabatic measurements and compare them with standard measurements. The investigation has been carried out with multiple turbochargers ranging from very small to medium passenger car size turbochargers. In the end, a possible application for the criterion is given.